Logistic Infrastructure, Informational Technology and Crop Production: Role of Food and Crop Production in Economic Miseries - Muhammad Ayub Mehar (International Journal of Public Finance)
This study examines the impacts of logistic facilities and infrastructure on crop and food production, inflation, and unemployment rates. It concludes that improvement in logistic facilities is an important significant and robust element of food and crop production growth. The logistic infrastructure improves employment in direct and indirect ways. Empirical evidence does not favor subsidies, tax exemptions, and credit to the private sector for crop production and food security enhancement. The study recognizes the importance of information technology for food and non-food crop production growth. Moreover, information technology improves the employment opportunities. These findings are based on 14 years data of 187 countries, while fixed and common effect models have been applied to estimate the parameters.